Peran Guru Pendidikan Agama Kristen dalam Pendidikan Etis-Teologis Mengatasi Dekadensi Moral di Tengah Era Disrupsi - Yonatan Alex Arifianto (Program Studi Pendidikan Agama Kristen, 2021)
The problem of students in dealing with moral decadence in socializing in the technological era is very risky and can clash spiritually. This problem will be a threat if the role of Christian religious education teachers does not maximize in seeking Biblical learning. Through descriptive qualitative methods, it can be concluded that teachers as educators in Ethical-Theological to overcome moral decadence in this period of disruption must be a priority for teachers and parents to work together in suppressing moral decadence. So what the teacher does is the first to know the nature of moral decadence and challenges in the era of disruption. So that it can provide solutions for students. Both teachers taught Christian ethical values from a biblical perspective as the basis for norms of life that are taught and applied in everyday life. And thirdly, Christian religious education teachers as role models in life wherever they are, especially in the virtual or digital world, this will have an impact on changes in students who see and imitate the teacher's attitude in the real and digital world community. Abstrak Persoalan peserta didik dalam menghadapi dekadensi moral dalam pergaulan di era teknologi sangat riskan dapat membenturkan kerohanian. Persoalan tersebut akan menjadi ancaman bila peran guru pendidikan agama Kristen tidak memaksimalkan dalam mengupayakan pembelajaran sesuai Alkitabiah. Melalui metode kualitatif deskritif dapat disimpulkan bahwa guru sebagai pendidik dalam Etis-Teologis untuk mengatasi dekadensi moral pada masa disrupsi ini harus menjadi prioritas guru dan orang tua untuk bekerja sama dalam menekan dekadensi moral. Maka yang dilakukan guru adalah yang pertama mengetahui hakikat dekadensi moral dan tantangan di era disrupsi. Sehingga dapat memberi solusi bagi peserta didik. Kedua guru mengajarkan nilai etika Kristen dalam persepektif Alkitab sebagai landasan norma kehidupan yang diajarkan dan diterapkan dalam kehidupan sehari hari. Dan yang ketiga Guru pendidikan Agama Kristen sebagai teladan dalam kehidupan dimanapun berada terlebih di dunia maya atau digital maka hal ini akan berdampak bagi perubahan peserta didik yang melihat dan meneladani sikap guru dalam berkomunitas didunia nyata maupun digital.